The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1108/jtf-12-2017-0057
|View full text |Cite
|
Sign up to set email alerts
|

Who am I if you can’t see me? The “self” of young travellers as driver of eWOM in social media

Abstract: Purpose The purpose of this paper is to analyse factors influencing the propensity to share travel experiences in social media during a trip, across a sample of Millennial and Generation Z consumers in three different countries. Design/methodology/approach An online survey was sent to consumers between 16 and 30 years in Sweden, UK and India. Structural equation modelling and multigroup analysis was conducted to compare results between countries and generations. Findings Young travellers’ need for uniquene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 34 publications
5
62
0
6
Order By: Relevance
“…There is a clear need to enhance the tourism use of the smartphones among the youngest group (16)(17)(18)(19), to promote the creation of positive feelings and emotions. The intermediate age group (20)(21)(22)(23)(24)(25)(26)(27)(28)(29) uses the tourist functionalities frequently and is characterized by a more neutral emotional behavior. Finally, the oldest age segment (30)(31)(32)(33)(34)(35)(36)(37)(38) requires strategies that combine the virtual and real worlds because, for them, smartphones by themselves do not generate any kind of feeling, which is the main trigger of eWOM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a clear need to enhance the tourism use of the smartphones among the youngest group (16)(17)(18)(19), to promote the creation of positive feelings and emotions. The intermediate age group (20)(21)(22)(23)(24)(25)(26)(27)(28)(29) uses the tourist functionalities frequently and is characterized by a more neutral emotional behavior. Finally, the oldest age segment (30)(31)(32)(33)(34)(35)(36)(37)(38) requires strategies that combine the virtual and real worlds because, for them, smartphones by themselves do not generate any kind of feeling, which is the main trigger of eWOM.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, in times of loneliness and boredom, for example, not being able to interact with other people, mainly through social networks, or to search for information or use entertainment apps, can trigger an acute case of nomophobia [68,70,71,74]. These effects underline the importance that people, particularly the youngest sector of the population, attach to the main values of the web 2.0 model that have given smartphones their protagonist role: multidirectional communication and universal access to information [1,10,24,25,40].…”
Section: Smartphones At the Service Of The Tourist Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…Free and fast connectivity was therefore found to be important for Millennials. Ek Styvén & Foster (2018) analysed factors influencing the propensity to share travel experiences in social media during a trip, across a sample of Millennial and generation Z (under 18) consumers in Sweden, UK and India. They found few significant differences between the two generations ort between countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lee and Youn (2009) argued that the persistence of investigating eWOM on these platforms remained to determine consumer purchase intentions. Meanwhile, as eWOM on social media was relatively new, therefore less importance was given initially to this platform, with limited number of studies Hussain et al, 2017;Lever, et al, 2017;Ek Styven and Foster, 2018). Recent studies have shown that consumers have been extensively using social media in order to get information about unfamiliar products and services (Ek Styven and Foster, 2018; Fang, 2014; Westerman, et al, 2014).…”
Section: Introductionmentioning
confidence: 99%